The Colorado Adoption Project - Rhea, Sally-Ann (2012)
This paper describes the Colorado Adoption Project (CAP), an ongoing genetically-informative longitudinal study of behavioral development. We describe the features of the adoption design used in CAP, and discuss how this type of design uses data from both parent-offspring and related- versus unrelated- sibling comparisons to estimate the importance of genetic and shared environmental influences for resemblance among family members. The paper provides an overview of CAP’s history, how subjects were ascertained, recruited, and retained, and the domains of assessment that have been explored since the CAP’s initiation in 1975. Findings from some representative papers that make use of data from CAP participants illustrate the study’s multifaceted nature as a parent-offspring and sibling behavioral genetic study, a study that parallels a complimentary twin study, a longitudinal study of development, a source of subjects for molecular genetic investigation, and a study of the outcomes of the adoption process itself. As subjects assessed first at age 1 approach age 40, we hope the CAP will establish itself as the first prospective adoption study of lifespan development.